Implementation Of Marketing Programs In Competitive Strategies In The Television Industry Based On Service Dominant Logic And Value Co-Creation - Robbiah Adawiyah; Endy Gunanto Marsasi (Amkop Management Accounting Review (AMAR), 2026)
Digitization has had a significant impact in the television sector in Indonesia, changing people's media consumption patterns and putting significant pressure on the television industry. This study aims to analyze the marketing and competitive strategies of Nusantara TV, particularly through the development of the "Culture of of Indonesia" program as a form of differentiation and the penerapan Service-Dominant Logic (SDL) and Value Co- Creation. Using a qualitative descriptive method through interviews, observations, and documentation during an internship, the study found that the shift of audiences to digital platforms requires television to produce more relevant and collaborative content. The "Culture of Indonesia" program serves as an instrument of co- creation with audiences and cultural communities to create more authentic, representative, and sustainable service values. The research results indicate that the application of SDL and cultural content differentiation strengthens Nusantara TV's position in facing media competition in the digital era.